Future-Ready Physicians: Exploring Medical Students’ Readiness, Attitudes, and Perceptions of Healthcare Artificial Intelligence in Saudi Arabia - Moria, Hassan Abdulaziz; Alatawi, Amirah; Alzahrani, Sharifah; Mirghani, Hyder; Al Shadfan, Hisham (UI Scholars Hub, 2025)
Background: While the integration of artificial intelligence (AI) in healthcare has advanced globally, there is limited research on the preparedness of medical students in the Tabuk region of Saudi Arabia, particularly regarding their specific educational needs and cultural context. This study assessed medical students’ knowledge, attitudes, readiness, and confidence toward AI integration at the University of Tabuk, providing the first comprehensive analysis of AI readiness in this underrepresented northern region of Saudi Arabia. Methods: A cross-sectional study was conducted among 261 medical students and interns across all academic years (1–6) at the Faculty of Medicine, University of Tabuk, using a validated questionnaire to measure AI knowledge, attitudes, perceptions, confidence, and readiness. Results: This study provides novel insights: students demonstrated limited AI knowledge (54.4% reported limited or average understanding) yet maintained predominantly positive attitudes (89.7% neutral/positive). A significant readiness–confidence gap was identified—73.2% supported AI curriculum integration, and most reported low confidence in practical AI application. The mean perception score of 24.3 ± 4.1 represents the first quantified AI readiness metric for medical students in northern Saudi Arabia. Conclusion: This study provides the first evidence-based framework for AI integration in medical education within the Tabuk region, revealing that positive attitudes coexist with significant knowledge and confidence deficits. These findings establish essential baseline metrics for developing culturally appropriate AI curricula for Saudi medical education.